STOMATOPOD AND DECAPOD CRUSTACEANS OF THE ARCHIPELAGO OF FERNANDO DE NORONHA, NORTHEAST BRAZIL - Fausto-Filho, José (Arquivos de Ciências do Mar, 2018)
The purpose of this study is to describe the stomatopod and decapod crustaceans of the Archipelago. This paper is more than just a check list and includes information about the systematics, ecology, bathymetric and geographical distribution of the species included.